Quotes in social media; a model of Islamic propagation on social media. - Hamdan, Hamdan (Jurnal Mercusuar, 2020)
This article aims to provide an initial description of a model of Islamic propagation called "Quotes in Socmed" and its use on social media. In addition to being literature-based, this research also has a qualitative approach because the presented data is descriptive, making it more of a descriptive analysis. There are several important aspects to this model, including the setting and layout, elements, and content. The layout, typography, color, and lighting in the visual design of this model are not determined by a fixed standard but are adjusted to the needs and conditions of the social media audience. The elements of the quote include a frame, background, preacher’s profile, and the message or quote itself. As the name suggests, the message should be as concise as possible but should still convey deep meaning and impact, immediately entering the thoughts or emotions of the audience and leaving a lasting impression.